In situ selective determination of methylmercury in river water by diffusive gradient in thin films technique (DGT) using baker's yeast (Saccharomyces cerevisiae) immobilized in agarose gel as binding phase - Tafurt-Cardona, Makenly [UNESP]; Eismann, Carlos Eduardo [UNESP]; Suárez, Carlos Alfredo [UNESP]; Menegário, Amauri Antonio [UNESP]; Silva Luko, Karen [UNESP]; Sargentini Junior, Ézio (Elsevier B. V., 2015)
Saccharomyces cerevisiae immobilized in agarose gel as binding phase and polyacrylamide as diffusive layer in the diffusive gradient in thin films technique (DGT) was used for selective determination of methylmercury (MeHg). Deployment tests showed good linearity in mass uptake up to 48 h (3276 ng). When coupling the DGT technique with Cold Vapor Atomic Fluorescence Spectrometry, the method has a limit of detection of 0.44 ng L(-1) (pre concentration factor of 11 for 48 h deployment). Diffusion coefficient of 7.03 ± 0.77 × 10(-6) cm(2) s(-1) at 23 °C in polyacrylamide gel (pH = 5.5 and ionic strength = 0.05 mol L(-1) NaCl) was obtained. Influence of ionic strength (from 0.0005 mol L(-1) to 0.1 mol L(-1) NaCl) and pH (from 3.5 to 8.5) on MeHg uptake were evaluated. For these range, recoveries of 84-105% and 84-98% were obtained for ionic strength and pH respectively. Potential interference due to presence of Cu, Fe, Mn, Zn was also assessed showing good recoveries (70-87%). The selectivity of the proposed approach was tested by deployments in solutions containing MeHg and Hg(II). Results obtained showed recoveries of 102-115 % for MeHg, while the uptake of Hg(II) was insignificant. The proposed approach was successfully employed for in situ measurements in the Negro River (Manaus-AM, Brazil).
Keywords: Mercury; Methylmercury; Passive sampler; Saccharomyces cerevisiae